2020
DOI: 10.1177/2059204320937224
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Research on Music Education and Child Development: Contributions and Challenges

Abstract: Based on a comprehensive analysis of 39 studies published in academic journals in the past decade (2010–2020), this article discusses the strengths of current research and the challenges that lie ahead for researchers interested in conducting longitudinal research on music education and child development. Among the strengths of the reviewed studies are multi-year projects, diverse study samples and programs, and a wide range of areas of interest—cognitive and neural to socioemotional and musical development. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 104 publications
2
15
0
Order By: Relevance
“…Our study explored the associations between musical and cognitive abilities on low SES children. The findings of weak relations between these abilities meet those from studies with higher SES children (e. g. Swaminathan et al, 2017;Swaminathan & Schellenberg, 2018;2020), Our analyses suggest distinctive abilities, in favor of the perspectives of multiple intelligences (Gardner, 1983) and of modularity (Peretz, 2009). Therefore, it is important to recognize different abilities as different potentials that children can explore.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our study explored the associations between musical and cognitive abilities on low SES children. The findings of weak relations between these abilities meet those from studies with higher SES children (e. g. Swaminathan et al, 2017;Swaminathan & Schellenberg, 2018;2020), Our analyses suggest distinctive abilities, in favor of the perspectives of multiple intelligences (Gardner, 1983) and of modularity (Peretz, 2009). Therefore, it is important to recognize different abilities as different potentials that children can explore.…”
Section: Discussionsupporting
confidence: 76%
“…Musical abilities of children with low SES improved with training (Habibi et al, 2018;Ilari et al, 2016). Yet, the few studies exploring specific relations between musical abilities and SES in childhood found no such relation (Degé et al, 2015;Swaminathan & Schellenberg, 2019;2020). This may be interpreted as additional evidence in favor of the independence of musical and cognitive abilities.…”
Section: Relationships Between Children's Musical Abilities and Cogni...mentioning
confidence: 95%
See 2 more Smart Citations
“…(6) Randomization: randomized or non-randomized group assignment (dichotomous variable). Random assignment is an important methodological aspect to establish causation, as it prevents self-selection effects, thereby minimizing the effects of potential pre-existing differences between groups (e.g., Ilari, 2020;Schellenberg, 2020a).…”
Section: Heterogeneitymentioning
confidence: 99%